Soul Stunting in Higher Education: Four Case Narratives from the Campus Counseling Room in Indonesia - Yeyentimalla Yeyentimalla (GHMJ (Global Health Management Journal), 2025)
Background: Soul stunting is a term used by the researcher to describe the arrested growth of a student’s inner life, characterized by difficulties in managing emotions, building healthy relationships, and responding wisely to life’s challenges. As both researcher and counselor, the author engaged directly with the participants in a real counseling setting, allowing for an authentic observation and intervention in their soul development. This condition often originates in family upbringing patterns and can persist into university years, affecting academic engagement, social relationships, and career readiness. While conceptual discussions on emotional intelligence and student development are abundant, most remain theoretical or survey-based, with limited impact on real behavioral change. The present study addresses that gap through an action-oriented, practice-based approach. The aim of the present study is to explore the phenomenon of soul stunting among university students through four real case narratives from the campus counseling room, focusing on five dimensions of soul development: emotional maturity, empathy, the ability to build healthy relationships, reflective rather than reactive thinking, and effective problem-solving. It also demonstrates how emotionally intelligent communication can serve as an effective strategy for restoring and strengthening these aspects of students’ soul development. Methods: This qualitative case study was conducted through real counseling experiences in diverse natural settings, including campus counseling rooms, cafés, practice fields, public spaces, social media, and WhatsApp conversations. The counselor, bringing more than two decades of cultivating emotionally intelligent communication skills, particularly through emotional discernment, served as the primary instrument for data collection and interpretation. Data were gathered through participant observation, in-depth interviews, and reflective field notes. Ethical considerations included concealing participant identities and omitting formal informed consent to preserve the natural flow of interactions and avoid behavioral manipulation. Results: Analysis of four authentic counseling narratives revealed that emotional discernment, as a form of tacit knowledge, plays a pivotal role in identifying, addressing, and transforming soul stunting. Conclusion: Findings offer practical implications for campus counseling services, policy-making, and family-based interventions.